2017
DOI: 10.1007/s00402-017-2762-3
|View full text |Cite
|
Sign up to set email alerts
|

The challenging surgical treatment of closed distal humerus fractures in elderly and octogenarian patients: radiographic and functional outcomes with a minimum follow-up of 24 months

Abstract: These study data seem to confirm our hypothesis that plate fixation for DHFs guarantees adequate fracture osteosynthesis and satisfactory functional outcomes at medium to long-term follow-up, not only in elderly patients, but also in octogenarian osteoporotic patients (≥85 years) with 13-C1 and 13-C2 fracture patterns, while an alternative solution should be considered for type C3 fractures, even in a primary trauma setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The number of patients in each study ranged from 5 to 181 ( Table I ). There was 1 RCT 32 and 26 case series 1 , 2 , 3 , 6 , 7 , 8 , 9 , 10 , 14 , 18 , 20 , 21 , 22 , 24 , 27 , 28 , 30 , 36 , 38 , 42 , 44 , 45 , 46 , 47 , 50 , 51 ( Table II ). Eight case series 8 , 9 , 20 , 21 , 22 , 30 , 45 , 51 were not clearly classified but were viewed as case series for the purpose of this review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of patients in each study ranged from 5 to 181 ( Table I ). There was 1 RCT 32 and 26 case series 1 , 2 , 3 , 6 , 7 , 8 , 9 , 10 , 14 , 18 , 20 , 21 , 22 , 24 , 27 , 28 , 30 , 36 , 38 , 42 , 44 , 45 , 46 , 47 , 50 , 51 ( Table II ). Eight case series 8 , 9 , 20 , 21 , 22 , 30 , 45 , 51 were not clearly classified but were viewed as case series for the purpose of this review.…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen articles met our inclusion criteria. There was one RCT, 32 14 retrospective, 1 , 3 , 6 , 9 , 14 , 20 , 21 , 22 , 24 , 28 , 42 , 45 , 46 , 51 and 3 prospective 8 , 30 , 50 case series. One study included both a prospective and a retrospective series.…”
Section: Resultsmentioning
confidence: 99%
“…Open reduction and internal fixation remain the gold standard treatment of intraarticular fractures of the distal humerus with the restoration of the articular surface being paramount [7,22]. Factors contributing to the complexity of these fractures are the small dimension of fragments which can limit screw fixation and osteoporosis requiring implants providing good bone purchase [12,16,23,24]. Despite advances in implant design, several retrospective studies still present high complication rates, moderate functional results, and high revision rates [9,14,25].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the evolution of surgical approaches and design of elbow-specific implants in the last decades, recent studies have failed to show significantly improved outcomes [7][8][9][10][11]. Malunion, nonunion, deformity, stiffness, heterotopic ossification, and complications from the olecranon osteotomy and the ulnar nerve are consistently reported and are mainly related to cartilage loss, inadequate reduction, and suboptimal fixation [4,[12][13][14][15]. Yetter et al reported recently in their systematic review and meta-analysis a total complication and reoperation rate of 53.4% and 20.8% respectively [15].…”
Section: Introductionmentioning
confidence: 99%
“…Compromised vasculature occurs in 2.6%-20% of cases of displaced SHFs in children [3][4][5][6], with two kinds of brachial artery injuries reported to be associated with SHFs: those presenting with a pale pulseless hand and those with a pink pulseless hand (PPH) which is well perfused without a palpable radial pulse [6][7][8]. While vascular compromise in elderly patients with SHFs is rare due to osteoporosis and low-energy trauma compared with pediatric patients, open reduction and plate xation was recommended for satisfactory outcomes [9]. In pediatric patients, urgent closed reduction and percutaneous pinning (CRPP) is the primary treatment in both situation, and vascular exploration is often required in the case of a pale pulseless hand [6][7][8][10][11].…”
Section: Introductionmentioning
confidence: 99%